The Impact of Using Discovery Learning on EFL Students’ Writing Skill - Satriani; Razaq, Yusuf; Nurhidayanti; Muzkiyah, Nurul (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The aims of the research are to enhance writing skills on hortatory exposition texts for the third year of MTs As’adiyah Putri 1 Sengkang. This research used a quasi-experimental method with two groups of pre-test and post-test designs. The subject of the research was the third-year students of MTs As’adiyah Putri 1 Sengkang. In this research, two classes were taken as samples. Class IX A was chosen as the experimental class and IX B as the control class. The experimental class consists of 25 students and 23 students from the control class. Writing tests (pretest and posttest) were used to collect data, which was then analyzed using descriptive and inferential statistics in SPSS. The results of the pre-test and post-test showed a significant enhancement. It was proven by the mean score of the students’ experimental post-test (74.96) is higher than the mean score of the students’ pre-test (55.44) and the t-test value of the post-test is 0.004, which is smaller than 0.05. The gain scores of both groups show enhancement in students’ writing skills. However, the gain score of the experimental class was higher than the control class. The gain score of the experimental class was 19.52. From this research finding, it showed that the use of discovery learning could enhance the students’ writing skills on hortatory exposition texts.